Chapter 12 Preventing Male Mental Illness in Post-war Britain - Haggett, Ali (2019)
Ali Haggett extends the boundaries of previous work, exploring the discourse around gender and prevention of mental illness in Britain from the 1950s. The chapter examines how important information about health and well-being was communicated to men, and in turn, how men conceptualised their own psychological well-being. Drawing on a range of printed primary sources and archival material, the chapter explores the medical, political and cultural context within which men and women negotiated ideas about their own well-being in post-war Britain. It argues that, for a range of complex reasons and competing exigencies, male mental health was almost entirely neglected-both reflecting and reinforcing prevailing assumptions about masculinity, coping and the image of the 'strong, silent man'.